Escalation of news reading preference in the post vicennial era of new media revolution - Abdul Rahman, Saiful Nujaimi; AlSagoff, Syed Agil; Md Ghani, Miharaini (Human Resource Management Academic Research Society, 2023)
The gradual degradation of conventional newspapers has become inevitable today. Just about a decade ago, compact newspaper was viewed as the most preferred public reading news medium “ and predicted to last for at least another 20 years. Ironically, its decline is no longer a mere speculation with the presence of new media “ online news platforms. This latest hybrid of journalistic medium has become the latest reading trend in today's era of post vicennial new media revolution. This new journalistic horizon, nevertheless, must be embraced by all media organizations with precise comprehension of its spiritual and physical demands and needs. Concisely, today's public reading preference has skewed to a fresher and simpler medium of news presentation “ the online news. This phenomenon has made many media organizations paused to restructure their operations to cater the demand and needs of the new horizon of communication. Hence, this paper began with a few queries “ among others are in finding out the areas of reformation that had been accomplished by the Malaysian media organizations in fulfilling the increasing demands of the public on online news, and in determining the key factors that triggered the change of reading preference among Malaysian. Findings of this research may alter our perceptions on how rapid the public attitude in gratifying their media as the source of information. Yielded results are expected to instil better understanding upon the possibilities of future threats and obstacles that may befall unto any news publication. In short, this paper aspires to generate better understanding on contemporary news' reading preference “ not only amongst Malaysians, but also in ensuring the future relevance of news representation throughout this digital millennium.